2011
DOI: 10.2172/1023469
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Design Report for the Remote-Handled Low-Level Waste Disposal Project

Abstract: This document addresses the conceptual design parameters associated with a proposed onsite remote-handled low-level waste disposal facility. A new onsite facility has been identified as an alternative for providing continued remote-handled low-level waste disposal capability in support of ongoing Department of Energy missions at the Idaho site. However, a decision has not been made by the Department of Energy to develop a new onsite disposal facility. The decision, following all required analyses and evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Cleanup and closure of INL's existing onsite disposal facility at the Radioactive Waste Management Complex (RWMC) will result in the need for a replacement facility. Several candidate locations for construction of this new facility have been considered (Harvego et al 2010a(Harvego et al , 2010b and two locations have been identified for further analysis.…”
Section: Project Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cleanup and closure of INL's existing onsite disposal facility at the Radioactive Waste Management Complex (RWMC) will result in the need for a replacement facility. Several candidate locations for construction of this new facility have been considered (Harvego et al 2010a(Harvego et al , 2010b and two locations have been identified for further analysis.…”
Section: Project Descriptionmentioning
confidence: 99%
“…Among them is a capability to safely handle and dispose of remote-handled low-level waste (RH LLW). In order to maintain this important capability, a new facility is proposed (Harvego 2010a(Harvego , 2010b. This report documents archival research and field investigations to identify cultural resources located in the two preferred alternative locations for construction of this new facility.…”
Section: Introductionmentioning
confidence: 99%